EXPRESSIVE ILLOCUTIONARY ACTS IN TAYLOR SWIFT’S COMMENCEMENT SPEECH AT NEW YORK UNIVERSITY 2022 - Kayla, Kayla Suci Ramadhani; Rido, Akhyar (Linguistics and Literature Journal, 2025)
This study analyzes the types and functions of expressive illocutionary acts found in Taylor Swift’s 2022 commencement speech atNew York University. The research applied Searle’s (1979) speech act theory as the main framework and used a qualitativedescriptive method. The data were collected from Swift’s speech transcript and analyzed based on the classification of expressive acts and their felicity conditions. The findings revealed that there are 42 expressive illocutionary acts representing 9 types of expressive acts, namely thanking, apologizing, congratulating, praising, complaining, protesting, boasting, lamenting, and welcoming. Among these, praising appears as the most dominant function, followed by complaining. The dominance of praising motivates the audienceand strengthens emotional connection, as well expresses admiration. On the other hand, complaining and lamenting acts are used strategically to express vulnerability and authenticity, which made the speech more relatable and persuasive to the audience. The research findings indicate that Taylor Swift employs expressive illocutionary acts to maintain a balance between emotion, humor, and authority in her message, which can help her to build solidarity with the audience, deliver inspiration, and emphasize the values of resilience and self-acceptance. Furthermore, this study can enhance the understanding of how expressive acts are used in publicspeaking and provide useful insights for further studies in pragmatics and speech analysis. Keywords: commencement speech, expressive illocutionary acts, pragmatics, qualitative study, speech act theory, Taylor Swift